UMPSA drives Student Empowerment Agenda - Mimi Rabita, Abd Wahit (UMPSA, 2023)
GAMBANG, 15 October 2023 - The Minister of Higher Education, Yang Berhormat Dato’ Seri Mohamed Khaled Nordin officiated the Open Day and 2023 Convocation Expo of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) at the Sports Complex Hall UMPSA Gambang Campus recently.